From a dwarf to a giant: Revalidation of Callulops valvifer (Barbour, 1910), (Amphibia, Anura, Microhylidae) - Günther, Rainer (Zootaxa, 2013)
According to the most recent revision of the subfamily Asterophryinae, the species Pomatops valvifera was considered to be a synonym of Phrynomantis (now Callulops) robusta. On the basis of recently collected material from near the type locality of Pomatops valvifera on the Bomberai Peninsula in western New Guinea, the invalidity of the genus name is confirmed but the species name is revalidated. Callulops valvifer (new combination) was hitherto unequivocally known from a single specimen of less than 30 mm snout-vent length. With a length of more than 70 mm for males and of more than 80 mm for females, this species is now among the largest of the currently known 22 species of the genus Callulops.